Da biopolítica à necropolítica contra os povos indígenas durante a ditadura militar brasileira (1964-1985) - Rodrigo Alvarenga; Elston Américo (Ciências Sociais Unisinos)
Considering the violations of the human rights of indigenous peoples during the military dictatorship period in Brazil, the present study aims to analyze such violations from the point of view of biopolitics, considering their development in the perspectives of Foucault, Agamben, and Mbembe, in order to demonstrate that the genocidal and ethnocidal practices of that period do not only derive from an exposition to death related to state racism or the typification of slaughterable life, but also consist in a deliberate practice of making die, which brings Brazilian indigenous politics of the period closer to a necropolitics.